TEACHING CLASSROOM CONTROVERSIES Navigating Complex Teaching Issues in the Age of Fake News and Alternative Facts - Bezalel, Glenn Y. (Routledge, 2024)
Teaching Classroom Controversies is the essential guide for all teachers trying to navigate their way through issues of controversy in the age of 'fake news' and 'alternative facts.